2018
DOI: 10.1177/1179552218787502
|View full text |Cite
|
Sign up to set email alerts
|

An Evidence-Based Review of Statin Use in Patients With Nonalcoholic Fatty Liver Disease

Abstract: Background:Nonalcoholic fatty liver disease (NAFLD) is a common complication in patients with metabolic syndrome. The role of statin therapy specifically for the treatment of NAFLD remains unknown. The aim of this review is to discuss outcomes of recent articles analyzing statin therapy in patients with NAFLD.Findings:A total of 12 trials met the inclusion criteria. Statins were not found to increase the prevalence of NAFLD once confounding variables were considered. Statins were also found to be beneficial in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 61 publications
1
43
0
2
Order By: Relevance
“…Our findings that liver fat may be an important mediator of the effect of cholesterol-lowering on T2D is consistent with a report showing that liver fat may help identify statin-taking individuals at risk of T2D (42). Finally, it is noteworthy that the HMGCR variant that lowers LDL-C is not associated with any significant change in liver enzymes, potentially reflecting the lack of an increase in NAFLD incidence seen with statin medications (43).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings that liver fat may be an important mediator of the effect of cholesterol-lowering on T2D is consistent with a report showing that liver fat may help identify statin-taking individuals at risk of T2D (42). Finally, it is noteworthy that the HMGCR variant that lowers LDL-C is not associated with any significant change in liver enzymes, potentially reflecting the lack of an increase in NAFLD incidence seen with statin medications (43).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with NAFLD do not present a higher risk for serious liver injury caused by statins, so they can be used to treat dyslipidemia in patients with NAFLD [6]. A recent review that included 12 trials regarding statin therapy in patients with NAFLD has shown that no study reported elevated liver enzymes caused by statin treatment, with some of them showing improved transaminase levels [10]. Lowering cholesterol level in dyslipidemic patients with very high cardiovascular risk reduces the incidence of both cardiovascular morbidity and mortality.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, metformin, statins, and fibrates, are currently being tested as NAFLD treatments in clinical trials. However, these drugs have significant adverse side effects, including enhanced risk of infection and osteoporosis (55)(56). Hence, novel treatment candidates with high efficacy and minimal side effects are urgently demanded for the treatment of NAFLD (57).…”
Section: Treatmentmentioning
confidence: 99%